GC-MS/FID/EAD: A method for combining mass spectrometry with gas chromatography-electroantennographic detection - Shuttleworth, Adam; Johnson, Steven D. (Frontiers in Ecology and Evolution, 2022)
Gas chromatography-electroantennographic detection (GC-EAD), typically combined with a flame ionization detector (FID), is a widely used technique for studying insect semiochemicals. Combining mass spectrometry (MS) with GC-EAD is extremely beneficial, but has seldom been adopted, possibly due to the practical challenges associated with incorporating an MS (under vacuum) into a GC-EAD system. We describe a novel method of incorporating MS into a GC-EAD system, where the FID is maintained in the system rather than being replaced by an MS. With this method, effluent is still split between EAD and FID, with the FID being used to assign components that elicit antennal responses, as in a normal GC-FID/EAD system. The MS is introduced via a second effluent splitter inserted before the split between the EAD and the FID. This method allows for EAD, FID and MS data to be obtained from a single injection, which is especially useful for analysis of thermally desorbed and solid-phase microextraction (SPME) samples. This configuration is also relatively simple to implement and resolves some of the practical challenges associated with dividing effluent between a detector at atmospheric pressure (a live antenna) and a detector under vacuum (the MS). We present test runs with hawkmoth antennae and floral volatiles to demonstrate the effectiveness of this system, and discuss the challenges and practical solutions to incorporating MS into a GC-EAD system that retains an FID detector.